Factors associated with utilization of antenatal care services among rural women, Telangana, India - Narayan Das, Biranchi; Kanakamedala, Seshasai; Mummadi, Mahesh kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Antenatal care is the essential health care extended to pregnant women. Complete antenatal health care includes four antenatal visits, 2 TT injections, and consumption of 100 Iron and Folic acid tablets. In Telangana state the proportion of mothers received full ante natal care in rural area is only 37.3%. Hence, the present study conducted with an objective to assess the factors associated with utilization of antenatal care services among rural women in Telangana state. Methods: The study is a community based cross sectional study. It was conducted in villages of Moinabad Mandal of Telangana state. Sample size was calculated to 373.Out of 26 villages 20 villages were chosen randomly and from each village 20 houses were selected by stratified random method. Married women delivered at least one child during last five years were included. Pretested questionnaire was administered. The data were tabulated in MS Excel and analyzed by SPSS. Results: Among 373 participants, 89.3% mothers registered during 1st trimester, 92.8% confirmed their pregnancy in the Government sector, 81.3% mothers had four or more antenatal visits, nearly 87.7% mothers received two doses of TT and 77.2% had taken more than 100 Iron tablets. The factors identified to be having statistically significant (p< 0.05) association with better utilization of antenatal care were age at child birth >25 years, education10th class and above, Working mothers, first child birth, Socioeconomic class I- IV and early registration. On application of simple logistic regression predictors were found to be age, education, occupation, birth order, SES and early registration. Conclusions: Awareness should be made by the ASHA workers, ANMs and Anganwadi workers through better education and motivation of the target groups such as young mothers, homemakers, low socio-economic status groups and late registered mothers for better utilization.